Enhancing Elementary Learners’ Vocabulary Mastery through Duolingo: A Study of Motivation and Learning Outcomes - Meida Fitriana; Tiara Noviarini (Universitas Muhammadiyah Lampung, 2025)
The use of game-based digital applications has become increasingly popular in English language teaching at the elementary school level due to their potential to create engaging and learner-centered environments. Such applications are particularly relevant for young learners, who require interactive and enjoyable learning experiences to maintain motivation and attention. This study aims to examine the effect of using the Duolingo application on students’ learning motivation and English vocabulary achievement in an elementary school context. A quantitative approach was employed using a quasi-experimental design with a nonequivalent control group. The participants consisted of 36 fifth-grade students, who were divided into an experimental group (18 students) and a control group (18 students). Data were collected through a learning motivation questionnaire and an English vocabulary achievement test comprising 20 multiple-choice items. The collected data were analyzed using normality tests, homogeneity tests, and an independent samples t-test to determine statistical significance. The results revealed a significant difference in both learning motivation and vocabulary achievement between students who learned using the Duolingo application and those who received conventional instruction. The mean post-test score of the experimental group (83.40) was higher than that of the control group (71.85), with a significance value of 0.002 < 0.05. These findings suggest that the integration of Duolingo contributes positively to both affective and cognitive learning outcomes. Therefore, the Duolingo application can be considered an effective supplementary tool for enhancing elementary school students’ motivation and English vocabulary mastery.